Optimizing Low-Pressure Die Casting of A356 Aluminum Alloy Wheel Rims: A Novel Side Core With Integrated Cooling System - Roni Kusnowo; Hanif Azis Budiarto; Cecep Ruskandi; Sophiadi Gunara; Ery Hidayat; Muhammad Nahrowi; Emma Dwi Ariyani (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study explores the development of a novel side core design with an integrated cooling system for the low-pressure die casting (LPDC) of A356 aluminum alloy wheel rims in Indonesia. The objective is to reduce cycle time and minimize casting defects. The methodology involves 3D modeling using SolidWorks and simulations performed with MAGMAsoft to evaluate filling and solidification behavior, air pressure, and air entrapment. Notably, this is the first application of a cooling system in Side cores within the Indonesian automotive industry, motivated by the need to improve production efficiency and product quality, as current manufacturing processes suffer from long cycle times and high defect rates. Simulation results show a significant reduction in cycle time by 72 seconds, improving both efficiency and product quality. This study demonstrates the effectiveness of integrating cooling systems into side cores to enhance the LPDC process.